C1‐Symmetric [Ir(C^N1)(C^N2)(O^O)]‐Tris‐Heteroleptic Iridium(III)‐Complexes with the Preferentially Horizontal Orientation for High‐Performance Near‐Infrared Organic Light‐Emitting Diodes. Issue 15 (6th May 2021) - Li, Wentao; Wang, Baowen; Miao, Tiezheng; Liu, Jiaxiang; Lü, Xingqiang; Fu, Guorui; Shi, Linxi; Chen, Zhongning; Qian, Pengcheng; Wong, Wai‐Yeung
Abstract: The development of high‐efficiency near‐infrared (NIR)‐emitting Ir(III)‐complex‐based phosphors for reliable NIR‐OLEDs (near‐infrared organic light‐emitting diodes) is still a formidable challenge. Herein, a molecule‐engineered approach is developed to afford three C 1 ‐symmetric [Ir(C^N 1 )(C^N 2 )(O^O)]‐ tris ‐heteroleptic Ir(III)‐complexes ([Ir(iqbt)(dFppy)(acac)] (1 ), [Ir(iqbt)(ppy)(acac)] (2 ), and [Ir(iqbt)(dpqx)(acac)] (3 )), whose good NIR‐luminescent efficiency (ΦPL  = 0.18 for 1 (λem  = 703 nm), 0.26 for 2 (λem  = 715 nm) or 0.28 for 3 (λem  = 707 nm)) originates from the strengthened 3 MLCT contribution (MLCT = metal‐to‐ligand charge transfer). Moreover, the quantitative molecular orientation determination of their doped emitting layers (EMLs) reveals that the preferentially horizontal orientation of the emitting dipoles is beneficial to their highly efficient NIR‐OLEDs with light out‐coupling. Especially for the NIR‐OLED ‐2 with λem  = 715 nm, a high performance (ηEQE Max  = 5.30% and negligible (<2%) efficiency‐roll‐off) is realized among the reported solution‐processed NIR‐OLEDs based on Ir(III)‐complexes at similar color gamut. This result shows that C 1 ‐symmetric [Ir(C^N 1 )(C^N 2 )(O^O)]‐ tris ‐heteroleptic Ir(III)‐complexes can provide a new platform to low‐cost and large‐area scalable NIR‐OLEDs. Abstract : Three new C 1 ‐symmetric [Ir(C^N 1 )(C^N 2 )(O^O)]‐ tris ‐heteroleptic Ir(III)‐complexes are developed for near‐infrared organic light‐emitting diodes (NIR‐OLEDs). Apart from the strengthened 3 MLCT (MLCT = metal‐to‐ligand charge transfer) effect, the preferentially horizontal orientation in their doped emitting layers is beneficial to the high‐performance solution‐processed NIR‐OLEDs with light‐coupling (ηEQE Max  = 5.30% at λem  = 715 nm with negligible efficiency‐roll‐off).